Practices and Attitudes of Women Regarding Family Planning And Menstrual Regulation in The Sylhet Division of Bangladesh - SM Zahedul Islam Chowdhury (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2020)
Several hundred thousand women in Bangladesh terminate their pregnancy either by menstrual regulation (MR) or through abortion. Government policy does not recognize abortion; but there exists a policy for MR, permitting termination of unwanted pregnancy up to 10 weeks from the last menstrual period. But access to safe MR is limited-unskilled and untrained providers mostly conduct termination of pregnancy; making unsafe abortion one of the leading causes of maternal deaths in Bangladesh. In order to reduce maternal mortality and morbidity in the country, some initiative was launched.The overall aim was to improve knowledge of and access to quality MR services for the prevention of unsafe abortion and unsafe MR. The present study will examine the impact of the MR intervention, i.e. how far the program has been successful in increasing awareness regarding timeline for safe MR. Findings suggest that overall respondents in the intervention area are much better off in terms of awareness regarding timeline of safe MR (79% of women) compared to their control group counterparts (51%), People belonging to different age groups (adolescents, adults, the aged) and socio economic categories (rich/poor, educated/illiterate) get the relevant message regarding WHY, WHEN, WHERE, and by WHOM the MR procedure should be performed. The implementing agencies have played a crucial role in promoting safe MR in their respective working areas in the aspects of awareness creation, standard guideline on MR, enabling environment, and rights based approach. However, there still remains scope to improve quality of care.